Biomarkers of Exposure for Dual Use of Electronic Cigarettes and Combustible Cigarettes: Nicotelline, NNAL, and Total Nicotine Equivalents. Issue 7 (13th December 2019) - Jacob, Peyton; St. Helen, Gideon; Yu, Lisa; Nardone, Natalie; Havel, Christopher; Cheung, Polly; Benowitz, Neal L
Abstract: Introduction: Dual use of electronic cigarettes (e-cigarettes) and combustible cigarettes is a major public health issue. It is generally accepted that exclusive e-cigarette use is less harmful than exclusive combustible cigarette use, but most e-cigarette users continue to smoke combustible cigarettes as well. To what extent the use of e-cigarettes reduces harm in people who continue to smoke combustible cigarettes has been debated. The aim of this study was to explore the utility of biomarkers as measures of dual use. Methods: In two human studies of participants who used e-cigarettes only or both combustible cigarettes and e-cigarettes, we measured urine concentrations of the metabolites of nicotine (total nicotine equivalents) as well as two biomarkers of tobacco exposure: 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), a tobacco-specific carcinogen metabolite, and nicotelline, a tobacco alkaloid not found in significant concentrations in e-cigarette products. Results: The presence of nicotine metabolites indicates either e-cigarette or combustible cigarette use. Nicotelline (half-life of 2–3 hours) indicates recent combustible cigarette use and NNAL (half-life of 10 days or more), indicates combustible cigarette use occurring within several weeks prior to sample collection. Conclusions: Nicotelline and NNAL are useful biomarkers for combustible tobacco use in users e-cigarettes. The application of these biomarkers provides a tool to help assess whether, or to what extent, dual use of e-cigarettes and combustible cigarettes reduces harm compared to sole use of combustible cigarettes. These biomarkers can also verify exclusive use of e-cigarettes over short (24 hour) or long (several week) time periods. Implications: : To what extent dual use of e-cigarettes and combustible cigarettes reduce harm compared to smoking combustible cigarettes only is of considerable public health interest. We show that the levels of the minor tobacco alkaloid nicotelline and the nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) are extremely low in electronic cigarette fluids. The urine biomarkers nicotelline and the NNK metabolite 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) are indicative of cigarette smoking and can be used to assess recent and past smoking in dual users.